On the non-conservative problem of the cantilevered beam - S. R. Martirosyan (National Academy of Sciences of Armenia)
The paper is devoted to the analysis of stability of the cantilevered beam with a concentrated mass and moment. Рассматривается задача устойчивости консольного упругого стержня, нагруженного «следящей» силой при наличии сосредоточенной инерционной массы и инерционного момента на свободном конце.
Keywords: Physics